PENGUATAN IDENTITAS DIGITAL DAN STRATEGI PROMOSI UMKM MELALUI PEMBUATAN QR CODE, PENDAFTARAN GOOGLE MAPS, DAN BANNER USAHA DI LINGKUNGAN II KELURAHAN SUKARAME BARU - Siti Afifah Azzahra; Nayla Yuri Natasya; Melanda Cahya Aqila; Rade Sidauruk; Vidia Tri Astuti; Muhammad Fadzry; Aldiva Mukhsin; Dwi Nugroho (CV. Denasya Smart Publisher, 2026)
Digital transformation requires Micro, Small, and Medium Enterprises (MSMEs) to establish a clear business identity and an integrated promotional strategy. Field observations conducted in Lingkungan II, Sukarame Baru Village, revealed that a number of MSME operators had not yet developed visual identity banners and had not registered their businesses on digital platforms such as Google Maps, resulting in limited visibility and marketing reach. This Community Service (PKM) activity aims to strengthen the digital identity of MSMEs and enhance the effectiveness of their promotional efforts through the creation of banners, QR Codes, and digital business location registration. The method employed was a participatory action approach, encompassing the stages of observation, planning, implementation, and evaluation carried out in collaboration with business operators. The results indicated a success rate of 90%, marked by improved business accessibility, greater ease for consumers in locating businesses, and an increased understanding among MSME operators of the importance of integrating offline and digital promotion. This program demonstrates that targeted strengthening of visual and digital identity is capable of sustainably improving the competitiveness of MSMEs in the digital economy era.